2014
DOI: 10.1097/cnj.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Spiritual Well-Being

Abstract: Understanding factors that influence spiritual wellbeing may improve nurses' spiritual caregiving. This study examined relationships between emotional intelligence (EI) and spiritual wellbeing (SWB) in undergraduate and graduate nursing students. Using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) and the Spiritual Well-Being Scale (SWBS), relationships were found between managing emotion and spiritual well-being, and managing emotion and existential well-being. Implications for education and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…Also, Studies showed a correlation between emotional intelligence and empathy (Hajibabaee, Farahani, Ameri, Salehi, & Hosseini, 2018). According these studies, empathy is one of emotional intelligence abilities identified as key components in spiritual well-being ( Beauvais et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Studies showed a correlation between emotional intelligence and empathy (Hajibabaee, Farahani, Ameri, Salehi, & Hosseini, 2018). According these studies, empathy is one of emotional intelligence abilities identified as key components in spiritual well-being ( Beauvais et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, we question whether the character of a clinician can affect the outcome of a patient, and how a clinician's character is influenced by SWB. Beauvais et al [49] examined the relationship between emotional intelligence (EI) and SWB in nursing students using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) and the Spiritual Well-Being Scale (SWBS). Results indicated relationships between managing emotion and spiritual and existential well-being.…”
Section: Religious/spiritual Well-beingmentioning
confidence: 99%
“…Based on the view of Bar-On, emotional intelligence is a set of capacities, beliefs, and non-cognitive skills and increases individual capabilities to successfully face challenges and environmental pressures ( 16 ). Several studies on emotional intelligence have indicated that individuals with higher emotional intelligence have more spiritual well-being( 17 ), lower mental disorders ( 18 ), lower possibility of suicide ( 19 ), higher self-efficacy ( 20 ), higher motivation ( 21 ), better problem-solving ( 22 ), and higher socio emotional adjustment ( 23 ). Also, several studies have been conducted on the relationship between emotional intelligence and critical thinking in baccalaureate nursing students and nurses, and some indicated a positive correlation between these 2 variables ( 24 - 27 ).…”
Section: Introductionmentioning
confidence: 99%